ENERGY POLICY FOR A SUSTAINABLE AND SECURE STATIONARY ENERGY SECTOR - outhred, h (185P -3466)
Human societies now face interlinked challenges in meeting their stationary energy requirements: Tightening flow constraints for crude oil and later natural gas[1] with associated upward pressure on prices of fossil fuels and the many goods and services that depend on them.Worsening environmental impacts, at the global level due to climate change emissions from the use of fossil fuels, as well as a wide variety of local and regional impacts [2] Water quantity and quality concerns due to environmental and human pressures [2,3]